Telaah Putusan MK dalam Sengketa PHPU Pilpres 2004 (Perspektif Negara Demokrasi Konstitusional) - Rahman Yasin (Jurnal Konstitusi, 2014)
This paper aims to examine the extent of the impact of the decision of the Constitutional Court of the Republic of Indonesia No. 1/PHPU.PRES-XII/2014 related PHPU 2014 presidential election dispute  in relation to  the  strengthening  of the constitutional legitimacy of the democratic state based on law and the constitution. Constitutional Court Decision No. 1/PHPU.PRES-XII/2014 gives importance to the development of our constitutional democratic system of government in the modern era. The Constitutional Court’s decision gives the meaning of democracy in a substantial sense of justice substantive. As a state agency to maintain and oversee the constitution, the Constitutional Court has been performing its functions and powers under the provisions of Section 24C of the 1945 Constitution and Law No. 24 of 2003 on the Constitutional Court. The Constitutional Court is a high state institution that is authorized through Section 24C of the 1945 Constitution, which is the authority to hear at the first and last are the final and binding nature of the decision, which among other things PHPU deciding the case, and based on Law No. 24 of 2003 as amended by Law Law No. 8 of 2011 concerning Amendment to Law Number 24 of 2003 on the Constitutional Court, and Article 29 paragraph (1) letter d Act No. 48 of 2009 on Judicial Power of the Constitutional Court, in essence the same, which is authorized to hear at the The first and last are the final and binding nature of the decision, including the case PHPU. In this sense the decision of the Constitutional Court put an end to various political opposition including the closing of all the dynamics of the political interpretation of the law that developed in the community.